Incorporating a Tourism Agenda in Public Archaeology Work - Medrana, Jack G. L. (Hukay; Vol 16, 2014)
Initiatives for the development of heritage tourism in a locality could be integrated in Public Archaeology. This is shown by a case study of the annual field schools of the Archaeological Studies Program of the University of the Philippines. There are at least five field schools where work of this kind has been done, namely in the Oriental Mindoro municipalities of Naujan, Bongabong, Bulalacao, and San Teodoro; and Opol, a municipality of Misamis Oriental. An archaeological project in El Nido, Palawan has also been included in this paper because it likewise has a thrust for Public Archaeology. From an examination of the work done in the field schools, it appears that a good program related to local tourism development includes an identification of stakeholders, making the development of local tourism a priority, identification of markets, and a strong sense of heritage among the cultural claimants.